A Comparative Study on the Health Status and Behavioral Lifestyle of Centenarians and Non-centenarians in Zhejiang Province, China—A Cross-Sectional Study - Rong, Chao; Shen, Shu-Hua; Xiao, Lu-Wei; Huang, Qi; Lu, Han-Ti; Wang, Hong-Xian; Li, Zheng-Xiang; Wang, Xiao-Ming (Frontiers in Public Health, 2019)
Background: The growth rate of centenarians was unusually rapid in recent decades, ushering in an era of longevity. This study aims to explore the difference between centenarians and non-centenarians using quantitative research, and to scientifically guide residents to develop the correct lifestyle and health care ways. Methods: From October 2013 to August 2017, A cross-sectional survey was conducted on 271centenarians and 570 non-centenarians by using the self-developed longevity and health questionnaire, who came from 29 counties and districts in 11 cities of Zhejiang province, China. 255 valid questionnaires were returned, with an effective response rate of 94.1%. Meanwhile, data of 526 non-centenarians from Zhejiang province was collected as a control group, with an effective response rate of 92.3%. Results: The prevalence rates of tumor, stomach and duodenal ulcer, diabetes, bronchial asthma and chronic obstructive pulmonary disease, tuberculosis among centenarians were all lower than those among non-centenarians. The oral health of centenarians is better than that of non-centenarians. The consumption of coarse cereals, pasta, other staple foods and fruits among centenarians was higher than that of non-centenarians. The percentage of centenarians who smoke or engage in recreational activities every day was lower than that of non-centenarians. Conclusions: We should give full play to the role of preventive medicine and health management to safeguard the health of residents. Pay attention to oral health, and develop the good habit of loving teeth. The diet should be rich and varied, and increase the intake of grains and fruits. Give up smoking, limit alcohol, spirit-preserving with calming, follow the law of scientific regimen.